Regulation of the extracellular signal-regulated kinase pathway in adult myocardium: differential roles of Gq/11, Gi and G12/13 proteins in signalling by α1-adrenergic, endothelin-1 and thrombin-sensitive protease-activated receptors - Snabaitis, Andrew K.; Muntendorf, Andreas; Wieland, Thomas; Avkiran, Metin (Cellular signalling, 2005)
Using adenoviruses encoding RGS2, RGS4 and Lsc (regulator of G protein signalling (RGS) domain of p115 RhoGEF), we investigated the contributions of G(q/11), Gi and G(12/13) proteins to G protein-coupled receptor (GPCR)-mediated activation of the extracellular signal-regulated kinase (ERK) pathway in adult rat ventricular myocytes (ARVM). Exposure to phenylephrine, endothelin-1 (ET-1) or thrombin induced significant activation of ERK1/2 and their downstream target 90 kDa ribosomal S6 kinase (p90RSK), which was abolished by overexpression of RGS4 (inhibits signalling via G(q/11) and Gi) or RGS2 (inhibits signalling via G(q/11)). Pertussis toxin (inhibits signalling via Gi) only partially attenuated the activation of ERK1/2 and p90(RSK) by phenylephrine and ET-1, but abolished such activation by thrombin. Overexpression of Lsc (inhibits signalling via G(12/13)) did not affect the responses to phenylephrine and ET-1, but suppressed the activation of ERK1/2 and p90RSK by thrombin. We conclude that full activation of the ERK pathway in ARVM by alpha1-adrenergic, ET-1 and thrombin receptors requires the activation of distinct families of heterotrimeric G proteins.